Equilibrium analysis of methylbenzene intermediates for a methanol-to-olefins process. Issue 5 (9th February 2016) - Cai, Dali; Wang, Qi; Jia, Zhao; Ma, Yunhai; Cui, Yu; Muhammad, Usman; Wang, Yao; Qian, Weizhong; Wei, Fei
Abstract : An Anderson–Schulz–Flory distribution in an MTO process comes from a thermodynamic equilibrium. Abstract : We propose an equilibrium analysis of methylbenzene intermediates for a methanol-to-olefins process based on an Anderson–Schulz–Flory distribution under commercial practical conditions. The key parameter was controlled by temperature. Such a study will give new insights into MTO and other chain growth processes.